Uji Larvasida Ekstrak Etanol Buah Mengkudu (Morinda citrifolia L.) terhadap Jentik Nyamuk Aedes Aegypti - Arimaswati Arimaswati; Sufiah Asri Mulyawati; Tien Tien; Pranita Aritrina; Nur Rahmi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Dengue Hemorrhagic Fever (DHF) is an endemic disease in Indonesia and includes acute viral infections from Flaviviridae family that are transmitted through intermediate host Aedes aegypti with symptoms of sudden high fever for two to seven days accompanied by bleeding. Noni fruit (Morinda citrifolia L.) contains active compounds as larvacide such as alkaloids, saponins, proxeronin and terpenoids. The purpose of this research is to know larvacide activity of ethanol extract of noni fruit to Aedes aegypti larvae death. This is an experimental research with post test only control group design. The sample used is 700 Aedes aegypti larvae which have reached III/IV instar and ethanol extract of noni fruit (Morinda citrifolia L.) divided into 5 concentrations, 0.5%, 1%, 2%, 4%, 8% and two control group namely negative control and positive control. Each treatment was repeated 4 times. The larvacide activity test was performed by observing the number of larvae deaths within 24 hours at 1 hour, 2 hour and 24 hour observation (5, 10, 15, 30, 60, 120, and 1440 min) and looking at the LC50 and LT50 values of the larvae tested. Result of this research shows that noni fruit (Morinda citrifolia L.) has a larvacide activity against the death of Aedes aegypti larvae. The Death of larvae was highest at 8% concentration with 100% death percentage in the 10 minutes and lowest at 0,5% concentration with 86% death percentage in the 1440 minutes. The probit analysis obtained LC50 in the 120 minutes is 1,44544% and LT50 at concentration of ethanol extract of noni fruit 2% is 70,8 minutes. From this research can be concluded that ethanol extract of noni fruit (Morinda citrifolia L.) has a larvacide activity to Aedes aegypti larvae death.